Integrated business projects - Olinzock, Anthony A.
Integrated Business Projects is project-based learning within a business scenario setting. Projects emphasize one of the main software applications (word processing, spreadsheet, presentation, and database), but with integration throughout. This text can be positioned to supplement any software tutorial within the computer applications curriculum